Bacterial community structure and putative nitrogen-cycling functional traits along a charosphere gradient under waterlogged conditions. (November 2021) - Yu, Mengjie; Su, Wei-qin; Huang, Laibin; Parikh, Sanjai J.; Tang, Caixian; Dahlgren, Randy A.; Xu, Jianming
Abstract: Unique spatial niches created by biochar form a dynamic biogeochemical soil zone, termed the "charosphere". Charosphere soil has different properties from either soil or biochar, often acting as a hotspot for microbial activity. However, the direction and magnitude of charosphere effects on soil processes and microbial communities remain inconclusive. Herein, we designed a multi-sectional box to separate charosphere soils from biochar under waterlogged conditions, investigating millimeter-scale changes in bacterial communities and distributions of specific genera across the charosphere created by pristine biochar (produced from corn stover at 300 °C), acid-modified biochar and washed biochar. The pristine biochar did not increase bacterial α-diversity but altered bacterial composition by promoting the growth of specific bacterial taxa and suppressing other species. In comparison, washed and acid-modified biochar increased the bacterial α-diversity. The pristine biochar significantly decreased N2 O emission and NO3 − concentration owing to a lower soil nitrification potential. Abundances of N-cycling functional taxa were higher in the near-charosphere than outer-charosphere zone, especially for Bacillus (N2 -fixation), MND1 (ammonia oxidation) and Rhodopseudomonas (denitrification). The spatial distribution of functional genes and genera documents the importance of heterogeneity within the charosphere gradient, providing a novel perspective into functional geometry to understand how biochar reduces N losses from agroecosystems. Highlights: Spatial distributions of N and functional bacteria were investigated at mm-scale resolution. Pristine biochar did not change bacterial diversity but altered community structure. Abundance of N-cycling taxa decreased with increasing distance from biochar source. Biochar decreased nitrification potential and hence N2 O emission.